Bugs and the Victorians - Clark, J. F. M. (John F. M.), 1963- (Yale University Press, 2009)
This text explores how science became increasingly important in 19th century British culture and how the systematic study of insects permitted entomologists to engage with the most pressing questions of Victorian times: the nature of God, mind, and governance, and the origins of life.